Clinical comparison of the AutoMicrobic system gram-positive identification card, API Staph-Ident, and conventional methods in the identification of coagulase-negative Staphylococcus spp. - Grasmick, A E (1983)
In an effort to rapidly identify coagulase-negative staphylococci (CNS), a clinical comparison was conducted with the AutoMicrobic system Gram-Positive Identification Card (GPI) (Vitek Systems, Inc.), the API Staph-Ident (Analytab Products), and the conventional methods of W. E. Kloos and K. H. Schleifer (W. E. Kloos and K. H. Schleifer, J. Clin. Microbiol. 1:82-88, 1975). CNS isolates tested included 157 from blood and 33 from urine in pure culture at greater than 10(5) CFU/ml. S. epidermidis accounted for 79.6 and 60.6% of the isolates from blood and urine, respectively. S. saprophyticus was the next most frequent urine isolate (27.4%). Other CNS species were isolated from blood and urine specimens with frequencies of less than 5%. Overall, the GPI correctly identified 158 (83.2%) of the 190 CNS, whereas the Staph-Ident identified 124 (65.3%) without further testing. This resulted in the GPI and Staph-Ident correctly identifying 95.9 and 74.5% of the S. epidermidis and 100 and 33% of the S. saprophyticus, respectively. The GPI misidentified 8 (47%) of the S. hominis and S. warneri isolates as S. saprophyticus, indicating the need for novobiocin testing. These data suggest that the GPI is a more definitive method for the rapid identification of S. epidermidis than the Staph-Ident and that both systems require additional testing to identify S. saprophyticus.